(untitled) (Research, Society and Development, 2022)
The participation of photovoltaic energy has increased its relevance on the world stage. This study aimed to evaluate whether solar tracking in photovoltaic systems, in addition to positively affecting energy generation, also impacts solar irradiance, temperature and efficiency, comparing them to a static system. Three photovoltaic modules were installed in Cascavel-PR, simulating the evaluated arrangements; a robust system to collect meteorological, thermal and electrical data for 365 days. Data were tabulated with hourly and monthly averages, by thermal range, occurrence density and irradiance. Analysis of Variance was used in order to compare the equality between the means. Then, applied the Tukey Test. As a main result, the lowest maximum temperature, the occurrence of the highest efficiencies and the highest energy production, stands out in the traceable arrangements. The final efficiency of the arrays, by range of irradiance, presented statistically different values, registering 7.27% for Arrangement 1; 10.38% for Arrangement 2 and 12.73% for Arrangement 3. The increase in production, compared to Arrangement 1, was 20.1% (Arrangement 2) and 37.2% (Arrangement 3). The correlations between irradiance, module temperature and energy production were similar, showing that the increase in irradiance caused higher module temperature and greater energy production, even with a reduction in efficiency.